Utility of whole‐body diffusion‐weighted magnetic resonance imaging in the management of treatment‐related neuroendocrine prostate cancer - Kurashina, Ryo (IJU Case Rep, 2020)
INTRODUCTION: Treatment‐related neuroendocrine prostate cancer, a rare and aggressive malignancy that emerges during androgen deprivation therapy characterized by low serum prostate‐specific antigen concentrations, is challenging to monitor because it is associated with predominantly visceral and lytic bone metastases. CASE PRESENTATION: We describe the case of a 69‐year‐old man with treatment‐related neuroendocrine prostate cancer in whom the treatment response could be monitored using whole‐body diffusion‐weighted magnetic resonance imaging in addition to serum concentrations of neuroendocrine markers. The patient responded well to platinum‐based chemotherapy and achieved a complete response, as evidenced by these diagnostic modalities. CONCLUSION: Our case suggests that whole‐body diffusion‐weighted magnetic resonance imaging is useful in disease management for treatment‐related neuroendocrine prostate cancer as well as the potential evaluation of mixed responses and treatment resistance.